Lung infection in orally inoculated SARS-CoV-2 hamsters - Evelyne Picard-Meyer; Marine Wasniewski; Franck Boué; Edgar Torres-Maravilla; Vinciane Saint-Criq; Thibaut Larcher; Kevyn Beissat; Elsa Jacouton; Sophie Holowacz; Anne-Judith Waligora-Dupriet; Philippe Langella; Alexandre Servat; et al. (PLoS ONE, 2025)
The digestive tropism of SARS-CoV-2 due to the presence of the same ACE2 receptor in the digestive system as in the respiratory system raised the question of the role of fecal-oral transmission in the pandemic. The aim of this study was to explore oral infection in hamsters model. SARS-CoV-2 inoculation via the oral and intranasal routes resulted in comparable infection in hamsters. In addition to implications for human health, oral infection could have implications for potential animal reservoirs.